The Correlation of Resilience With Nurses Work Stress In Emergency Unit Rumah Sakit Al Islam (RSAI) Bandung - Andria Pragholapati; Iyus Yosef; Irman Soemantri (Sorume Health Sciences Journal, 2020)
Work stressors in the Emergency Unit is higher compared with the stressors in other units. The high level of work stressors can cause to job stress. Each individu actually has an ability to adapt and being flexible when they were faced to the internal and external pressure which is known by the term resiliency. The purpose of this research is to know know the relationship between job stress resiliency in nurses who worked in the emergency unit Rumah Sakit Al Islam (RSAI) Bandung. Research conducted by descriptive correlative method using a total sampling so that all nurses in the Emergency Unit of Al Islam Hospital is 19 people. To examine the resiliency measure used RAS (Resiliency Attitudes Scale), whereas the work stress used job stress measuring device that were constructed based on the aspects of work stress expressed by Ivancevich and Matteson (1980). Test results obtained using T scores for univariate analysis and Mc Nemar for the bivariate analysis, using alpha significance value of 5% (α = 0.05). Based on it obtained value was calculated = 0.04 3.841 = 0.05; 1 the Ho accepted, this indicates there was no association between the occurrence of workplace stress with resiliency in nurses who work in the emergency unit of Rumah Sakit Al Islam (RSAI ) Bandung. [U1]Lowercase and separated by comma, consists of 3 to 6 phrases or words.